Design of a sustainable rainwater harvesting system - Tan, Keng Lim (2022)
Rainwater harvesting system (RWHS) is a system of collecting rainwater from impervious surfaces and storing it for future use. Although Malaysia has cheap water bills compared to other countries, Malaysia still experiences numerous water crises and water disruptions each year due to high water consumption or water pollution. This indirectly makes it difficult for stray animals to find water. Therefore, an animal-centric sustainable RWHS is a good solution for the problems mentioned above since Malaysia has a high average annual rainfall. The focus of this study was to design a RWHS for 10 stray cats and 25 kittens living in the Greater Gombak Animal Shelter (3°15'20.4"N, 101°43'53.3"E). In order to obtain the dimension of the office and select the appropriate sizes for the components, an on-site meeting was held with representatives of the animal shelter. Besides, Gombak Km16 was found to be the closest rainfall station to the animal shelter and its station number (3217001) was used in the following steps. First, the calculated roof catchment area on one of the longer sides of the hipped roof was 16.97 m2 . After applying the corresponding formula, the average rainfall intensity calculated for 20-year average recurrence interval and 5-minutes storm duration for this study area was 276.68 mm/hr. Taking the roof catchment area and average rainfall intensity as the reference indicators, the minimum effective cross-sectional area of the k-style gutter was 5000 m2 and the minimum nominal size of the round downspout was 85 mm. Then, the minimum tank size required calculated by the Tangki Nahrim 2.0 software was 0.2 m3 after considering the rainfall data from 1974 until 2016. A tank of this size had water 99.9% of the time and was capable of meeting the cats’ total daily water consumption of 5.375 litres. A filter was also installed in this RWHS to filter the collected rainwater and provide the cats with clean drinking water. In addition, this RWHS was fitted with a special design that utilizes hydrostatic pressure to supply filtered rainwater to three cages at a time by opening the valve. Lastly, sipper water bottles were also installed on the cage so that the cat could drink by licking the nozzle ball without causing water accumulation. The collected rainwater was safe for animals to drink as it was classified as good quality water after water sampling and testing. Overall, this RWHS was a good long-term investment because it cost less than RM3000.